554 ראנאלוגיה - הירש, אלי (מכאן, 2016)
This essay presents an interpretation of the relationship between Rana, the protagonist and name-bearer of Hedva Harechavi’s sixth poetry collection, and some of the other central characters in Harechavi’s poetry such as the characters named Ruth and Batia and the psychoanalyst Rena Mozes-Hrushovski. Rana is divine in nature: she embodies mythological dimensions and metaphysical consequences which set her entirely apart from Ruth, Batia and Moses-Hrushovski, who are bounded by their distinctive earthliness. Moreover, Harechavi’s poetry is unequivocal regarding a crucial aspect of the identity of these three characters: they are all clinical psychologists. The interpretation presented is based on two propositions. First, the article proposes viewing the characters of Ruth, Batia and Mozes-Hrushovski as earthly reincarnations of Rana; that is, her reflection and her materialization. Second, it proposes viewing the process in which Rana is reflected and materialized in these characters, and how she ultimately breaks free from their bounded earthliness and appears in all her mythical and metaphysical glory, as a journey of creative recollecting. In this journey, a godlike figure that had appeared to the poet at the dawn of time, but was since tainted and forgotten, reemerges in a slow and complex process, leading to her complete revelation as Rana. Only then, in this complete revelation, we recognize her unity throughout her reincarnations. In other words, it is not only Rana who emerges in Rana, but also Rana’s epic, which is narrated throughout all of Harechavi’s poetry books, ending in Rana and beginning in an unknown time – “the time before the time of world history”.